Estimation and dispersion modeling of landing and take-off (LTO) cycle emissions from Ataturk International Airport (vol 11, pg 153, 2018) - Kuzu, S. Levent (SPRINGER INTERNATIONAL PUBLISHING AG, 2018)
The original publication's Fig. 6 caption was incorrectly written as Fig. 6 Distribution of annual NOx concentrations (a). Distribution of annual NOx concentrations (b). Distribution of 8-h CO concentrations (c).
Keywords: Environmental Sciences & Ecology